Effects of Residential Environment and Lifestyle on Atopic Eczema Among Preschool Children in Shenzhen, China - Liu, Yanlin; Sun, Shujie; Zhang, Duo; Li, Wenchen; Duan, Zhenya; Lu, Shaoyou (Frontiers in Public Health, 2022)
Eczema, one of the most prevalent inflammatory skin diseases among children, is potentially influenced by genetic, environmental and social factors. However, few studies have investigated the effect of residential environment and lifestyle on childhood eczema. Therefore, this study conducted a cross-sectional study based on 2,781 preschool children in Shenzhen, China, during 2015–2016. Logistic regression models were employed to analyze the associations between residential/household environment, lifestyle, dietary habits and eczema in children. The prevalence of eczema among children in Shenzhen was 24.6%. Significant associations (increased odds >50%, P < 0.05) were found between childhood eczema and the factors of using composite wood floors (adjusted OR = 1.777 for doctor-diagnosed eczema, 1.911 for eczema-like symptoms), living in a villa/townhouse (aOR = 3.102, 2.156), the presence of mold or damp stains in the child's room (aOR = 1.807, 2.279), and rarely cleaning the child's room (aOR = 1.513, 1.540). In addition, watching TV/playing computer games for more than one hour per day was significantly associated with eczema (aOR = 1.172, 1.174). Notably, we found that eating rice/pasta one to three times per week may elevate the risk of eczema-like symptoms (aOR = 1.343), which warrants further investigation. In addition, ambient air pollution, in the covariates, may also affect childhood eczema. Therefore, avoiding these adverse factors and creating a low-risk environment are crucial to prevent childhood eczema.